The relevance of industrial/organisational psychology research in "post" colonial/apartheid South Africa : exploring the views of academics - Christison, Michael Alan (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
This dissertation explored the views of academics who teach and research in the area of Industrial/Organisational Psychology in South Africa about the utility of the field in engaging with the post-1994 South African workplace, thereby remaining relevant. When it emerged as a field of study and practice, Industrial/Organisational Psychology research's aim was to inform workplace practice and contribute to the betterment of society. It appears as if today this research is deemed irrelevant to the workplace and society, with many practitioners relying on their own knowledge and irrelevant repetitive one size-fit-all Euro-American developed theoretical framework and research evidence to solve the challenges of the post-1994 South African workplace, and to serve its society. The latter propelled the researcher to ask broadly the question of relevancy of the discipline in meeting the demands of the post-1994 South African workplace. Face-to-face, semi-structured interviews were employed to collect data on 8 senior and younger generations of academics in 3 different universities. The collected data was analysed using Braun and Clarke's 6 steps of thematic analysis. The data and study as a whole was approached with a 'post'-colonial lens and a Contexualist paradigm in order to contextualise in the present time the past nuances that arose in our country during the colonial and apartheid eras. Themes discussed seemed to indicate a lack of research focus by academics and their students due to limited time and stringent bureaucratic publication structures present both within their universities and outside. When it came to the discipline as seen through the lens of the data and what this suggested in terms of speaking to post-1994 workplace organisational psychological problems, the study found that the findings arising out of the research in I/O psychology appear to be of little relevance to whom they are currently aimed, leading to the idea of these studies acting as a change agent in the workplace and society to fall to the wayside.
Keywords: Psychology, Industrial -- Research -- South Africa